An analytical model of geosynthetic-reinforcement pile-supported embankments simultaneously considering pile–soil differential settlement and geosynthetic-soil interface friction - Rong Sun; Xin Jiang; Canyang Cui; Jianbiao Du; Lei Zhang; Hanyan Gu; Yanjun Qiu (European Journal of Environmental and Civil Engineering, 2026)

Quaternary evaporite sedimentation and potassium enrichment mechanism in Mahai Salt Lake, Qaidam Basin - Zihao Cui; Yanjun Zhao; Chenglin Liu; Pengyu Long; Yufei Hu; Ju Jiao; Jingjing Liu (Sedimentary Geology, 2026)

A dual-functional heterosalt additive enables synergistic interphase-bulk engineering for advanced nickel-rich cathodes - Dongni Zhao; Jing Luo; Zixiang Su; Hongzeng Dou; Jingzuo He; Junwei Zhang; Yanjun Zhao; Xinfang Xu; Peng Wang; Ningshuang Zhang; Xiaoling Cui; Shiyou Li (Chemical Engineering Journal, 2026)

The mediator subunit PagMED20 is associated with enhanced vegetative growth and photosynthetic performance in poplar - Xiao Wang; Changwen Xu; Ce Zhang; Xuandong Liu; Binghe Wang; Yanjun Li; Jinxing Lin; Yaning Cui (Journal of Plant Physiology, 2026)

Long-term petroleum pollution alters soil microbial communities via electron transfer capacity: Evidence from a 35-year chronosequence - Chengze Yu; Mingxiao Li; Jun Cui; Yanjun Xin; Ran Song; Wangmi Chen; Jiaqi Hou; Jianbing Li; Huibin Du; Beidou Xi (Journal of Environmental Sciences, 2026)

Stability analytical solution for the geosynthetic-reinforced pile-supported embankments based on an improved three-wedge model - Rong Sun; Xin Jiang; Canyang Cui; Jianbiao Du; Hanyan Gu; Yanjun Qiu (Geotextiles and Geomembranes, 2026)

New insights into the temporal speciation of phosphorus during anaerobic digestion of wetland biomass wastes - Fan Yu; Junxia Wang; Zhi Wang; Lan Mu; Xutong Wang; Qianqian Guo; Xiaoqiang Cui; Yanjun Hu; Beibei Yan; Guanyi Chen (Bioresource Technology, 2026)

Quality deterioration and its molecular basis in postharvest Flammulina filiformis: Insights from physiological and transcriptomic profiling under simulated storage environments - Yan Wang; Chong Shi; Yanjun Duan; Haikuo Cui; Jianxing Zhai; Zilong Deng; Benard Muinde Kimatu; Donglu Fang (Postharvest Biology and Technology, 2026)

Taurine attenuates heat stress-induced intestinal permeability by inhibiting endoplasmic reticulum stress and modulating gut microbiota - Haoran Jiang; Fan Mo; Zhuobin Pan; Chong Wang; Yanjun Cui (Journal of Thermal Biology, 2026)

Belowground reorganization complements canopy regulation in stabilizing yield formation of dual-planting cotton - Jingyuan Zhou; Lijie Zhan; Dongmei Zhang; Shizhen Xu; Zhenhuai Li; Yanjun Zhang; Jianlong Dai; Zhengpeng Cui; Xiaoli Tian; Hezhong Dong (Field Crops Research, 2026)

A pH/heating-driven curdlan-based complementary hydrogel for promoting full-thickness skin wound healing - Qingchen Cui; Linrong Yu; Jiahe Miao; Yanjun Wei; ShanShan Du; Xianggen Wu (Carbohydrate Polymers, 2026)

Early cotton topping increases peanut yield without sacrificing cotton yield through reducing interspecific competition under intercropping - Junjun Nie; Yanan Li; Zhenhuai Li; Shizhen Xu; Zhengpeng Cui; Lijie Zhan; Dongmei Zhang; Lin Sun; Jianlong Dai; Yanjun Zhang; Hezhong Dong (Field Crops Research, 2026)

Enzyme immobilization on nanomaterials in food industry: current status and future perspectives - Lang Du; Yingzhuo Liang; Sifan Cui; Jianyang Wei; Jianqiao Liu; Shuling Zhang; Yuqing Zhang; Liya Zhou; Ying He; Li Ma; Jing Gao; Yanjun Jiang (Critical Reviews in Food Science and Nutrition, 2026)

Improving S2S Precipitation Forecast over China via a Deep Learning Model with Multi-Sphere Causality-Linked Predictors - Bin Mu; Hao Guo; Shijin Yuan; Yuxuan Chen; Yuehan Cui; Yanjun Huang (Journal of Meteorological Research, 2026)

Shading-induced canopy cooling alleviates waterlogging damage during flowering by disrupting heat synergism in field-grown cotton - Yanjun Zhang; Yabin Yuan; Shizhen Xu; Zhenhuai Li; Zhengpeng Cui; Lijie Zhan; Dongmei Zhang; Junjun Nie; Lin Sun; Jianlong Dai; Hezhong Dong (Field Crops Research, 2025)

Enhanced Type-II singlet oxygen production via 3D topological porphyrin-based covalent organic framework - Xiaoning Zhan; Yucheng Jin; Houhe Pan; Baoqiu Yu; Rong Jiang; Boce Cui; Dongdong Qi; Siyu Liu; Yanjun Zhao; Jianzhuang Jiang (Chemical Engineering Journal, 2025)

Spatiotemporal diversification enables sustainable cotton-soybean production with enhanced yield and reduced emissions - Qingqing Lv; Ning He; Baojie Chi; Shizhen Xu; Zhenhuai Li; Li Wang; Yanjun Zhang; Dongmei Zhang; Zhengpeng Cui; Jianlong Dai; Junjun Nie; Yongjiang Zhang; et al. (Journal of Cleaner Production, 2025)

Acid-resistant microporous polyether nanofiltration membrane with high permeability for wastewater treatment - Chuanqi Zhang; Yanjun Zeng; Dan Lu; Yuxin Tao; Zhikan Yao; Saisai Lin; Yunlong Cui; Lin Zhang (Chemical Engineering Journal, 2025)

Pulled GA signal orchestration proteome reconfiguration and redundancy cycling via PtGA2ox10-mediated metabolic gatekeeping in Chinese pine seeds - Xinxiu Zuo; Shuai Liu; Yanjun Li; Yanyan Zhang; Duxian Lu; Shihui Niu; Xiaojuan Li; Jinxing Lin; Yaning Cui (Plant Cell Reports, 2025)

Mitigating waterlogging-induced yield loss in cotton through removal of early fruits: Agronomic and physiological mechanisms - Yanjun Zhang; Shen Qiu; Tiantian Liang; Shizhen Xu; Zhenhuai Li; Zhengpeng Cui; Lijie Zhan; Dongmei Zhang; Junjun Nie; Lin Sun; Jianlong Dai; Hezhong Dong (Field Crops Research, 2025)

Preparation, characterization and antimicrobial properties of double lysine-modified chitosan and its preservation ability in chicken meat refrigeration - Bin Dong; Yijie Wang; Lili Han; Guirong Cui; Yanjun Lin; Zhiwei Su; Guozhong Zhao (Food Chemistry, 2025)

Detection of table grape berries need to be removed before thinning based on deep learning - Wensheng Du; Xiao Cui; Yanjun Zhu; Ping Liu (Computers and Electronics in Agriculture, 2025)

Adsorption of polycyclic aromatic hydrocarbons (PAHs) in soil and water on pyrochars: A review - Lishi Tang; Panpan Wang; Chengze Yu; Ning Jiang; Jiaqi Hou; Jun Cui; Shuaishuai Xin; Yanjun Xin; Mingxiao Li (Journal of Environmental Chemical Engineering, 2025)

A MOF-derived Fe3O4/Fe0/Fe3C-2-600 dual-cathode electro-Fenton system construction: Revealing the mechanism for active centers linked by Fe0 as an electronic transfer station for enhancing Fenton reaction - Chuan Cao; Yanjun Guo; Dadi Chen; Jun Cui; Xiang Hu (Chemical Engineering Journal, 2025)

Engineered hydrogel platform for diabetic wound healing - Jidan Cui; Jianbin Shi; Yanjun Liu; Xianbao Shi; Jin Sun; Zhonggui He; Cong Luo; Shenwu Zhang (Chemical Engineering Journal, 2025)

Early-Middle Holocene climate change and its impact on the succession of Neolithic cultures in southern Hangzhou Bay - Jing Lu; Haiwei Zhang; Rui Zhang; Jiahui Cui; Yanyan Bao; Xiaowen Niu; Yanjun Cai; Hai Cheng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Evaluating and locating a suitable bedrock drilling site near zhongshan station with airborne and ground-based observations - Yanjun Li; Xiangbin Cui; Gang Qiao; Lin Li; Shinan Lang (Polar Science, 2024)

Analytical model of three-dimensional concentric ellipsoidal soil arching in geosynthetic-reinforced pile-supported embankments - Rong Sun; Xin Jiang; Lei Zhang; Canyang Cui; Zhengxian Li; Yanjun Qiu (Geotextiles and Geomembranes, 2024)

Characteristics of biofilms on polylactic acid microplastics and their inhibitory effects on the growth of rice seedlings: A comparative study of petroleum-based microplastics - Yizhuo Chen; Bo Cui; Yuhang Dou; Huiyu Fan; Yanjun Fang; Lei Wang; Zhenghua Duan (Journal of Hazardous Materials, 2024)

Deficit irrigation combined with a high planting density optimizes root and soil water–nitrogen distribution to enhance cotton productivity in arid regions - Fengquan Wu; Qiuxiang Tang; Jianping Cui; Liwen Tian; Rensong Guo; Liang Wang; Zipiao Zheng; Na Zhang; Yanjun Zhang; Tao Lin (Field Crops Research, 2024)

R-Q@P-D nanoparticle for improving the oral bioavailability and therapeutic efficacy: A novel reversible dual-target-mild-inhibition intestinal metabolic enzymes strategy for resveratrol delivery - Qingchen Cui; Yanling Li; Liping Zhou; Zongtao Liu; Yanjun Wei; Weihao Dong; Xianggen Wu (Chemical Engineering Journal, 2024)

In vitro antimicrobial activity of the novel antimicrobial peptide mytimacin-4 and its influence on the microbial community and quality of pork during refrigerated storage - Bin Dong; Yijie Wang; Guirong Cui; Yuna Wang; Yanjun Lin; Zhiwei Su; Guozhong Zhao (Food Control, 2024)

Enhancing stand establishment and yield formation of cotton with multiple drip irrigation during emergence in saline fields of Southern Xinjiang - Jianlong Dai; Zhengpeng Cui; Yanjun Zhang; Lijie Zhan; JunJun Nie; Jianqiang Cui; Dongmei Zhang; Shizhen Xu; Lin Sun; Bing Chen; Hezhong Dong (Field Crops Research, 2024)

A new method for generating equidistant/equiratio line between two points on the earth ellipsoid - Jianhui Zhang; Ruiquan Fu; Yanjun Cui; Shaoyang Chen; Mingjie Li; Xuefeng Zhang (Computers & Geosciences, 2024)

A carrier-free injectable hydrogel self-assembled using natural thymol and glycyrrhizin for MRSA-infected wound healing in rats - Zhengwei Cui; Xiaolu Zhang; Liping Zhou; Weihao Dong; Yanjun Wei; Zongtao Liu; Xianggen Wu (Chemical Engineering Journal, 2024)

Repurposing the KCa3.1 Blocker Senicapoc for Ischemic Stroke - Ruth D. Lee; Yi-Je Chen; Hai M. Nguyen; Latika Singh; Connor J. Dietrich; Benjamin R. Pyles; Yanjun Cui; Jonathan R. Weinstein; Heike Wulff (Translational Stroke Research, 2024)
Senicapoc, a small molecule inhibitor of the calcium-activated potassium channel KCa3.1, was safe and well-tolerated in clinical trials for sickle cell anemia. We previously reported proof-of-concept data suggesting that both pharmacological inhibition and genetic deletion of KCa3.1 reduces infarction and improves neurologic recovery in rodents by attenuating neuroinflammation. Here we evaluated the potential of repurposing senicapoc for ischemic stroke. In cultured microglia, senicapoc inhibited KCa3.1 currents with an IC 50 of 7 nM, reduced Ca 2+ signaling induced by the purinergic agonist ATP, suppressed expression of pro-inflammatory cytokines and enzymes (iNOS and COX-2), and prevented induction of the inflammasome component NLRP3 . When transient middle cerebral artery occlusion (tMCAO, 60 min) was induced in male C57BL/6 J mice, twice daily administration of senicapoc at 10 and 40 mg/kg starting 12 h after reperfusion dose-dependently reduced infarct area determined by T2-weighted magnetic resonance imaging (MRI) and improved neurological deficit on day 8. Ultra-high-performance liquid chromatography/mass spectrometry analysis of total and free brain concentrations demonstrated sufficient KCa3.1 target engagement. Senicapoc treatment significantly reduced microglia/macrophage and T cell infiltration and activation and attenuated neuronal death. A different treatment paradigm with senicapoc started at 3 h and MRI on day 3 and day 8 revealed that senicapoc reduces secondary infarct growth and suppresses expression of inflammation markers, including T cell cytokines in the brain. Lastly, we demonstrated that senicapoc does not impair the proteolytic activity of tissue plasminogen activator (tPA) in vitro. We suggest that senicapoc could be repurposed as an adjunctive immunocytoprotective agent for combination with reperfusion therapy for ischemic stroke.

Decoding PFAS contamination via Raman spectroscopy: A combined DFT and machine learning investigation - Yangxiu Chen; Yanjun Yang; Jiaheng Cui; Hong Zhang; Yiping Zhao (Journal of Hazardous Materials, 2024)

Progression of an emission inventory of China integrating CO2 with air pollutants: A chance to learn the influence of development on emissions - Guorui Zhi; Jinhong Du; Aizhong Chen; Wenjing Jin; Na Ying; Zhihui Huang; Peng Xu; Di Wang; Jinghua Ma; Yuzhe Zhang; Jiabao Qu; Hao Zhang; et al. (Atmospheric Environment, 2024)

Obtention, interaction, and characterization of the soy protein isolate-glycyrrhizin nanocomplex for encapsulating naringenin - Qingchen Cui; Xixi Song; Mengshuang Li; Yanjun Wei; Juan Dong; Xianggen Wu (Food Hydrocolloids, 2023)

Cotton yield stability achieved through manipulation of vegetative branching and photoassimilate partitioning under reduced seedling density and double seedlings per hole - Jingyuan Zhou; JunJun Nie; Xiangqiang Kong; Jianlong Dai; Yanjun Zhang; Dongmei Zhang; Zhengpeng Cui; Ziqing Hua; Zhenhuai Li; Hezhong Dong (Field Crops Research, 2023)

Distributions of total mercury and methylmercury and regulating factors in lake water and surface sediment in the cold-arid Wuliangsuhai Lake region - Zhimou Cui; Xiaohong Shi; Shengnan Zhao; Junping Lu; Zhiqiang Tian; Hao Zhang; Xin Guo; Yanjun Wang (Environmental Geochemistry and Health, 2023)

Terminal removal at first square enhances vegetative branching to increase seedcotton yield at low plant density - Junjun Nie; Lin Sun; Lijie Zhan; Xue Li; Wenting Hou; Yanjun Zhang; Weijiang Li; Dongmei Zhang; Zhengpeng Cui; Zhenhuai Li; Shizhen Xu; Jianlong Dai; et al. (Field Crops Research, 2023)

Ridge intertillage alters rhizosphere bacterial communities and plant physiology to reduce yield loss of waterlogged cotton - Yanjun Zhang; Shizhen Xu; Guangya Liu; Tengxiang Lian; Zhenhuai Li; Tiantian Liang; Dongmei Zhang; Zhengpeng Cui; Lijie Zhan; Lin Sun; Junjun Nie; Jianlong Dai; et al. (Field Crops Research, 2023)

MLRD-Net: 3D multiscale local cross-channel residual denoising network for MRI-based brain tumor segmentation - Xue Chen; Yanjun Peng; Yanfei Guo; Jindong Sun; Dapeng Li; Jianming Cui (Medical & Biological Engineering & Computing, 2022)

Investigation on oxygen-controlled sewage sludge carbonization with low temperature: from thermal behavior to three-phase product properties - Fan Yu; Yanjun Hu; Lianming Li; Qianqian Guo; Yonghao Zhu; Long Jiao; Yihong Wang; Xiaoqiang Cui (Environmental Science and Pollution Research, 2022)

Identification of Benign and Malignant Lung Nodules in CT Images Based on Ensemble Learning Method - Yifei Xu; Shijie Wang; Xiaoqian Sun; Yanjun Yang; Jiaxing Fan; Wenwen Jin; Yingyue Li; Fangchu Su; Weihua Zhang; Qingli Cui; Yanhui Hu; Sheng Wang; et al. (Interdisciplinary Sciences: Computational Life Sciences, 2022)

Identification of hub lncRNA ceRNAs in multiple sclerosis based on ceRNA mechanisms - Yanjun Ding; Taotao Li; Xinwei Yan; Mintian Cui; Chao Wang; Situo Wang; Fengmin Zhang; Ruijie Zhang (Molecular Genetics and Genomics, 2021)

Source Apportionment and Ecological-Health Risks Assessment of Heavy Metals in Topsoil Near a Factory, Central China - Jia Li; Guangcai Wang; Fei Liu; Linfeng Cui; Yanjun Jiao (Exposure and Health, 2021)

Faba Bean Organs Differed in Their Effects on Maize Seed Germination Rate and Soil Microbial Activities as well as Their Decomposition Patterns in a Regosol Soil - Zhibin He; Luhua Yao; Xuefeng Zhang; Yang Li; Dengke Wang; Lin Kang; Cui Cui; Aiying Huang; Ruiji Yang; Qianlin Xiao; Yanjun Guo (Journal of Soil Science and Plant Nutrition, 2020)

Transplantation of UC-MSCs on collagen scaffold activates follicles in dormant ovaries of POF patients with long history of infertility - Lijun Ding; Guijun Yan; Bin Wang; Lu Xu; Yan Gu; Tong Ru; Xiaoying Cui; Lei Lei; Jingyu Liu; Xiaoqiang Sheng; Bin Wang; Chunxue Zhang; et al. (Science China Life Sciences, 2018)

Transcriptome analysis reveals that constant heat stress modifies the metabolism and structure of the porcine longissimus dorsi skeletal muscle - Yue Hao; Yuejin Feng; Peige Yang; Yanjun Cui; Jiru Liu; Chunhe Yang; Xianhong Gu (Molecular Genetics and Genomics, 2016)

Occurrence and Partitioning of Antibiotics in the Water Column and Bottom Sediments from the Intertidal Zone in the Bohai Bay, China - Dengmiao Cheng; Yujia Xie; Yanjun Yu; Xinhui Liu; Shengnan Zhao; Baoshan Cui; Junhong Bai (Wetlands, 2016)

Risk factors of severe hand, foot and mouth disease complicated with cardiopulmonary collapse - Chunlan Song; Cheng Yibing; Yanjun Guo; Zhipeng Jin; Yajie Cui; Xue Gu (Infectious Diseases, 2015)

Behavior of expansive soils stabilized with fly ash - Fusheng Zha; Songyu Liu; Yanjun Du; Kerui Cui (Natural Hazards, 2008)

Study of 1998 heavy rainfall over the Yangtze River Basin using TRMM data - Cheng Minghu; He Huizhong; Mao Dongyan; Qi Yanjun; Cui Zhehu; Zhou Fengxian (Advances in Atmospheric Sciences, 2001)